Dialogue derailed : Joseph Ratzinger's war against pluralist theology - Mong, Ambrose Ih-Ren (Eugene, Oregon : PICKWICK, 2015)
Joseph Ratzinger has shaped and guided the church's understanding of its mission to proclaim the good news, as well as to forge good relations with non-Catholic Christian communities, other religious traditions, and with the secular world at large. Through a critique of Ratzinger's theology, this books draws attention to the importance of theological discourses originating from non-European contexts. Mong highlights the gap between a dogmatic understanding of the faith and the pastoral realities of the Asian church, as well as the difficulties faced by Asian theologians trying to make their voices heard in a church still dominated by Western thinking. While Mong concurs with much of Ratzinger's analysis of the problem in modern society, such as the aggressive secularism and crisis of faith in Europe-- he focuses attention on the realities of religious pluralism in Asia, which require the church to adopt a different approach in its theological formulations and pastoral practices.
Perspective of the Federation of Asian Bishop's Conferences
Includes bibliographical references and index.
Keywords: Benedict XVI, Pope 1927--; Religions -- Relations; Religious pluralism; Christianity and other religions